The Stopping Powers and CSDA Range for Positron and Electron in Human Kidney, Lung and Thyroid Organs - Dlshad, Hawar M.; Rashid, Jamal M. (East European Journal of Physics, 2026)
This study computed the stopping power of positrons in a few biological tissues in the energy range of 100 eV to 1 MeV. The base of the method is using the modified Bethe-Bloch expression for stopping power and effective atomic number analytical expression including key parameters such as the mean excitation energies of the target atoms that significantly impact stopping power results. Analytical formulas were mostly used to calculate the stopping power and continuous slowing down approximation CSDA range. The calculated results of the stopping power and range for positrons in a few compounds, such as kidney, lung and thyroid tissue are compared with other calculation results like Penelope 2012 program. Monte Carlo simulation was used for the calculations. The results were plotted in graphs to show the contrasts. And they satisfy a recognized need in the medical physics community for tissue-specific positron interaction data, with immediate applications in improving positron emission tomography (PET) image quantification accuracy and refining radiation dose for emitting radiopharmaceuticals.